THE INFLUENCE OF TIME PRESSURE, ROLE AMBIGUITY, WORKLOAD AND LACK OF MOTIVATION ON EMPLOYEE PERFORMANCE - KAREL TJAHJADI; FINKA PUTRIANA CAHYADI (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2020)
This study aimed to determine the influence of Time Pressure, Role Ambiguity, Workload, and Lack of Motivation on Employee Performance at PT XYZ. The population of this study was all of the employees at PT XYZ. 76 respondents were chosen to be the sample of this research. The sampling technique used was purposive sampling. The questionnaire was a 26-item likert scale, created by using google form, and distributed to the respondents via email. To analyze the data, research used multiple regression analysis as a test tool. Results showed that both Role Ambiguity and Lack of Motivation have a negative and significant influence on employee performance at PT XYZ, while the two other variables, Time Pressure and Workload don’t have any influence on employee performance.